Mechanism analysis of pore structure and crystalline phase of thermal insulation bricks with high municipal sewage sludge content. (10th December 2020) - Zhou, Wentao; Yang, Fengming; Zhu, Ruijian; Dai, Ge; Wang, Weijie; Wang, Wenlong; Guo, Xinli; Jiang, Jinyang; Wang, Zengmei
Highlights: Nano-pores introduced by silica fume affected thermal conductivity and strength. Effects of amorphous phase on thermal conductivity of bricks were analyzed. Effects of pore structure and continuous dense phase were quantified. Thermal insulation properties and strength performance were enhanced simultaneously. Abstract: As the inevitable by-product of sewage treatment, millions of tons of municipal sewage sludge (MSS) are increasingly stockpiled every year around the globe, creating enormous pressure on the environment and society. The preparation of porous insulation bricks based on MSS is put forward to realize environment protection and waste reclamation. However, the excessive amount of MSS will lead to the deterioration of strength and durability in the bricks. In this paper, the pore structure and crystalline phase of bricks were adjusted by the introduction of the ultra-fine amorphous phase, to improve the thermal insulation performance as well as the compressive strength. The thermal conductivity of the bricks could reach the lowest value of 0.194 W/(m·K) with the compressive strength of 10.2 MPa. Under the requirement of the mechanical strength, adding 3% of borax into bricks can increase the compressive strength to 18.8 MPa. The effects of the continuous dense phase and pore structure on thermal conductivity and compressive strength of bricks were investigated in reference to Bauer and Gibson model, respectively. The results provide a development direction for the preparation of thermal insulation bricks with high content MSS and alleviating the pressure of the shortage of clay.